(untitled) (Global Journal of Science Frontier Research, 2022)
A systematic investigation was carried out on the diseases and insect pests of coconut and areca palm in Wenchang City of Hain Province from 2019 to 2022 Stem bleeding disease coconut blackheaded caterpillar CBC coconut leaf beetle CLB and red palm weevil were found to be the main threats to coconut trees yellow leaf disease YLD leaf yellowing virus disease LYVD bacterial leaf spot disease CLB and Tirathabarufivena Walker were observed to be key restricting factors for the areca palm trees During this survey 17 species of plants were found as hosts of CBC YLD and LYVD were observed in five towns including Wencheng and Chongxing necrotic ringspot virus disease was discovered for the first time in Wencheng and Huiwen Currently As the major diseases and insect pests of coconut and areca palm presents a tendency of increasingly serious trend of in Wenchang City it is recommended that the agriculture and forestry departments to carry out integrated measures including regular monitoring forecasting and timely prevention and control once an outbreak trend is observed so as to ensure the sustainable and healthy development of the industries